Single Incision non-thoracoscopic Nuss procedure for children with pectus excavatum: protocol for a multicenter, non-masked, randomized controlled trial - Quan Wang; Quan Wang; Zhengxia Pan; Chun Wu; Yonggang Li; Gang Wang; Jiangtao Dai; Chunnian Ren; Chunnian Ren; Yiming Xie; Liangjun Xiong; Libing Zhang; et al. (Frontiers in Surgery, 2023)
BackgroundNuss procedure is the most common method of surgical treatment to pectus excavatum (PE). A significant percentage of surgeons choose to use thoracoscopic assistance during the Nuss procedure (TNP) to avoid cardiac injury. However, our previous findings confirm the safety of single incision Non-thoracoscopic Nuss Procedure (SINTNP). Hence, Further studies, particularly prospective randomized controlled trials, are necessary to assess the value of SINTNP for PE.MethodsThis study is a prospective, superiority, multicenter, non-masked, randomized controlled trial that investigates the outcome and hospitalization medical expense of SINTNP compared to TNP for PE. A total of 320 eligible patients according to sample size calculation by retrospective data will be randomly assigned to the SINTNP group or the TNP group at a 1:1 ratio using stratified blocked randomization and the zone length was set as four. Patients aged between 3 and 18 years old for the first surgery and without combination of complex anomalies such as Marfan syndrome and congenital heart disease will be considered for the study. The co-primary endpoint is thoracic related complications and medical expense during hospitalization. Thoracic related complications were defined as pneumothorax, pleural effusion, pneumonia and incision infection. The secondary endpoints include surgery duration and length of hospital stay.The registration number for this study protocol is ChiCTR230073081 (Chinese Clinical Trial Registry, A Primary Registry of International Clinical Trial Registry Platform, World Health Organization).